Seed morphology of Boschniakia sensu lato (Orobanchaceae) and its taxonomical implications - Piwowarczyk, Renata (Phytotaxa, 2015)
Seeds of 25 samples of 4 species of the holoparasitic genus Boschniakia sensu lato were investigated using light and scanning electron microscopy. Previous phylogenetic and morphological evidence indicated the division of Boschniakia s.l. into three genera: Boschniakia, Kopsiopsis, and Xylanche. However, results of the recent phylogenetic analysis are that Kopsiopsis hookeri and K. strobilacea are sister taxa in one lineage and Boschniakia himalaica and B. rossica are sister taxa in a different lineage. Differences in seed size and sculpture can be very auxiliaries in determining the taxonomic position of these species. In this study, analysis of the morphology of seeds showed the presence of three types of seed. The most significant is differences between the distinct type of seed B. rossica and B. himalaica. The usefulness of micromorphological studies on seeds is demonstrated. A comparison of the main characteristics distinguishing the seeds of Boschniakia s.l. is also presented and discussed.